Correlation of serum C - reactive protein with clinical parameters in diabetic patients having chronic periodontitis before and after treatment - Arkhawan Ali Abdulhaq; Ziwar Ahmed Salih; Solaf Abdulqadir Mustafa (Erbil Dental Journal)
Background and Objectives: Chronic periodontitis is an infectious disease characterized by inflammation within the supporting tissues of the teeth, progressive attachment loss, and bone loss. C-reactive protein, are acute phase proteins monitored as a marker of inflammatory status. The present study was performed to determine whether presence of periodontitis and non-surgical periodontal therapy could influence the serum levels of CRP in type II diabetes mellitus disease patients.